Unrevealing the therapeutic potential of artesunate against emerging zoonotic Babesia microti infection in the murine model - Fazilani, Saqib Ali; An, Wei; Li, Sihong; Hassan, Mohammad Farooque; Ishfaq, Muhammad; Lakho, Shakeel Ahmed; Farooque, Muhammad; Shoaib, Muhammad; Zhang, Xiuying (Frontiers in Veterinary Science, 2024)
Babesiosis a zoonotic blood protozoal disease, threatens humans and animals and is difficult to treat due to growing antimicrobial resistance. The study aimed to investigate the therapeutic efficacy of Artesunate (AS), a well-known derivative of artemisinin, observed against Babesia microti (B. microti) using a murine infection model. Male BALB/c mice (6 weeks old, 15 per group) were chosen and randomly divided into 1) Control group, 2) B. microti group, and 3) B. microti + Artesunate treatment groups. AS treatment at 2 mg/kg, 4 mg/kg, and 8 mg/kg of body weight significantly (P < 0.05) reduced the B. microti load in blood smears in a dose-dependent manner. Additionally, AS treatment mitigated the decrease in body weight and restored the normal state of the liver and spleen viscera index compared to the B. microti-infected group after 28 days. Hematological analysis revealed significant increases in RBC, WBC, and PLT counts post-AS treatment compared to the B. microti-infected group. Furthermore, AS administration resulted in significant reductions in total protein, bilirubin, ALT, AST, and ALP levels, along with mitigated liver and spleen inflammation and lesions as observed through histopathological analysis. AS also elicited dose-dependent changes in mRNA and protein expression levels of apoptotic, proinflammatory, and anti-inflammatory cytokines in the liver compared to control and B. microti-infected groups. Immunolabeling revealed decreased expression of apoptotic and inflammation-related proteins in AS-treated hepatic cytoplasm compared to the B. microti-infected group. AS also dose-dependently decreased apoptotic protein and increased Bcl-2. Overall, these findings underscore the potential of AS as an antimicrobial candidate in combating B. microti pathogenesis in an in vivo infection model, suggesting its promise for clinical trials as a treatment for babesiosis.